Volitional Weight-Lifting in Rats Promotes Adaptation via Performance and Muscle Morphology prior to Gains in Muscle Mass. (January 2014) - Rader, Erik P.; Miller, G. Roger; Chetlin, Robert D.; Wirth, Oliver; Baker, Brent A.
Investigation of volitional animal models of resistance training has been instrumental in our understanding of adaptive training. However, these studies have lacked reactive force measurements, a precise performance measure, and morphological analysis at a distinct phase of training - when initial strength gains precede muscle hypertrophy. Our aim was to expose rats to one month of training (70 or 700 g load) on a custom-designed weight-lifting apparatus for analysis of reactive forces and muscle morphology prior to muscle hypertrophy. Exclusively following 700 g load training, forces increased by 21% whereas muscle masses remained unaltered. For soleus (SOL) and tibialis anterior (TA) muscles, 700 g load training increased muscle fiber number per unit area by ~20% and decreased muscle fiber area by ~20%. Additionally, number of muscle fibers per section increased by 18% for SOL muscles. These results establish that distinct morphological alterations accompany early strength gains in a volitional animal model of load-dependent adaptive resistance training.